1992
DOI: 10.1002/jcb.240501320
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate endpoint biomarkers for chemoprevention

Abstract: The understanding of intermediate endpoint biomarker expression in relation to the sequential events in bladder tumorigenesis establishes a useful approach for evaluating chemopreventive agents. Biomarkers may be genotypic or phenotypic and function as biomarkers of susceptibility, exposure, effect, or disease. This paper reviews several years of research on biomarkers and their use in monitoring chemoprevention therapy. In initial animal experiments, mice were dosed with Kbutyl-N(4-hydroxybutyl)nitrosamine (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Four nonexclusive mechanisms may produce field disease: (i) hypersusceptibility of all the cells in a bladder resulting from inherited heterozygosity for a defective suppressor function (35,36), (ii) widespread genotypic changes from carcinogenic exposure affecting a significant portion or all of the bladder epithelium that increases the pool of cells immediately susceptible to ultimate carcinogenic conversion (37), (iii) altered growth and differentiation resulting from alterations in the complex tissue ecology induced by cytokines secreted by tumor cells (38), and (iv) "seeding" of either tumor or dysplastic cells from a single precursor lesion (25) (24). We suggest that by using quantitative phenotypic marker profiles the way is now open to investigate the cancer risk faced by an individual.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four nonexclusive mechanisms may produce field disease: (i) hypersusceptibility of all the cells in a bladder resulting from inherited heterozygosity for a defective suppressor function (35,36), (ii) widespread genotypic changes from carcinogenic exposure affecting a significant portion or all of the bladder epithelium that increases the pool of cells immediately susceptible to ultimate carcinogenic conversion (37), (iii) altered growth and differentiation resulting from alterations in the complex tissue ecology induced by cytokines secreted by tumor cells (38), and (iv) "seeding" of either tumor or dysplastic cells from a single precursor lesion (25) (24). We suggest that by using quantitative phenotypic marker profiles the way is now open to investigate the cancer risk faced by an individual.…”
Section: Resultsmentioning
confidence: 99%
“…A corresponding negative control slide omitting primary antibodies was also prepared. All reagent concentrations were optimized to achieve saturation of cellular binding sites (22,24). Each batch of reagent was individually titrated to determine the appropriate concentration that produced saturation and, hence, proportionality between immunofluorescence and the target biomolecule.…”
Section: Methodsmentioning
confidence: 99%
“…TCC is associated with a urothelial field change [25][26][27]. Random bladder biopsy or histologic mapping of cys tectomy specimens reveals a high incidence of atypia and carcinoma in situ in grossly normal urothelium.…”
Section: Discussionmentioning
confidence: 99%
“…13 DNA5cER, the percentage of cells with a DNA content of more than 5c, is a marker of overall genetic instability. 15 Previous studies from our laboratory showed the feasibility of measuring these 2 markers simultaneously on archived fine-needle aspiration slides by quantitative fluorescence image analysis (QFIA), and over-expression of both markers might be potential risk indicators for developing breast cancer. 16 The QFIA approach allows the analysis of multiple cellular markers simultaneously on single-cell basis after the completion of conventional morphological evaluation on the same slide; therefore, the conventional morphological evaluation would not be compromised.…”
mentioning
confidence: 99%